Evaluation of fracture parameters of NiTi shape memory alloy using digital image correlation - Shafaghi, Nima. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2013., 2013)
In this work, Digital Image Correlation (DIC) is used to investigate the e ect of martensitic phase transformation on fracture behavior of NiTi shape memory alloy. To nd out the e ect of phase transformation from austenite to martensite on fracture behavior of NiTi shape memory alloy, fracture tests were conducted at both room temperature where phase transformation occurs and at the temperature that prevents this transformation. Displacement eld that was obtained using DIC was used to estimate critical stress intensity factor. Results were compared to the ones obtained using linear elastic fracture mechanics (LEFM) and nite elements (FE). Before testing NiTi, the whole process was done using aluminum to validate the method. To characterize the NiTi, tensile tests at both temperatures were done and material properties were extracted. An experimental method based on DIC measurements was applied to estimate the size of martensitic phase zone and the result was compared to previous theoretical studies.
Keywords: Fracture mechanics.; Elastic solids.